The Renminbi central parity: An empirical investigation - Yin-Wong Cheung; Cho-Hoi Hui; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
On August 11, 2015, China revamped its procedure for setting the official central parity of the renminbi (RMB) against the US dollar. Our empirical investigation suggests that the intertemporal dynamics of China's central parity shifted after this policy change, though the deviation of the RMB offshore rate from the central parity and the US dollar index remained the two significant determi-nants of central parity after the policy change. In contrast, the VIX index only offered explanatory power up to August 2015. Thereafter, the onshore RMB rate and the difference between the one-month offshore and onshore RMB forward points have significant impacts on the central parity. While the US dollar index effect remains, we find no evidence of a rate-fixing role for the RMB exchange rate against the currency basket announced by China in December 2015.
URN:NBN:fi:bof-201705121291
Keywords: F31; F33; G15; G17; G18; 330